PENGARUH LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN PADA PT. BANK SYARIAH MANDIRI - NOVA SYAFRINA; SUDARMIN MANIK (Prodi Manaj. Perbankan Syariah Fakultas Ekonomi dan Bisnis Islam – UIN Imam Bonjol Padang, 2018)
This research was conducted at PT. Bank Syariah Mandiri Branch Office Flamboyan Subdistrict Tapung. The purpose of this study was to determine how much influence the work environment on employee performance at PT. Bank Syariah Mandiri Branch Office Flamboyan Subdistrict Tapung. The population and sample in this study are all employees of PT. Bank Syariah Mandiri Flamboyan Sub-Branch Office, Tapung Subdistrict, totaling 32 people. While the data analysis in this study uses the test of validity, reliability, simple linear regression, test coefficient of determination and t test. The results of this research hypothesis indicate that the work environment has a positive and significant effect on employee performance at PT. Bank Syariah Mandiri Branch Office Flamboyan Subdistrict Tapung. While the influence of the work environment on employee performance at PT. Bank Syariah Mandiri Flamboyan Sub-Branch Office Tapung District is 56.3% and the rest is influenced by other variables not examined in this study.